2011
DOI: 10.1108/14691931111097890
|View full text |Cite
|
Sign up to set email alerts
|

Organizational knowledge assets and innovation capability

Abstract: PurposeOrganizational knowledge assets are key organizational factors responsible for firm innovation, as well as effective management. Traditionally, a good piece of research takes the innovation processes from an external perspective, leaving aside the internal complexity that characterizes innovation dynamics. Nevertheless, the innovation capability of a certain firm depends very closely on the intellectual assets and organizational knowledge that it possesses, as well as on its ability to deploy them. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 57 publications
3
84
0
6
Order By: Relevance
“…In the literature, innovation is considered an important element of firm success [12]. Harper and Becker [13] indicated that innovation resulted in significant change-preferably an improvement in the real product, process, or service-that exceeds the impact of previous achievements; these authors further indicated that innovation supported sustainable business management.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, innovation is considered an important element of firm success [12]. Harper and Becker [13] indicated that innovation resulted in significant change-preferably an improvement in the real product, process, or service-that exceeds the impact of previous achievements; these authors further indicated that innovation supported sustainable business management.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the investigation cast light on the approaches to KM in small businesses and provide practical guidance and assistance to small businesses in their KM endeavours. As noted previously, knowledge assets are key factors responsible for organisational innovation and effective management (Delgado-Verde, Castro, & Navas-Lopez, 2011). Small businesses can develop the capacity to enhance their knowledge assets by effectively implementing KM.…”
Section: Research Questions and Significance Of Studymentioning
confidence: 99%
“…A knowledge-based perspective is the primary key for having successful organizations. However, it is also important to use dynamic approach on assessing intangible assets (Delgado-verde et al, 2011). According to Martin (2008), successful firms normally maintain strong human resources with good experiences and could contribute to firms through team-work activities.…”
Section: Introductionmentioning
confidence: 99%